Propulsi Kapal Listrik dengan Motor BLDC IPM: Analisis Kinerja dan Efisiensi - Dewi Rianti Mandasari; Budi Sudiarto; Lia Amelia; Cuk Supriyadi Ali Nandar (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2024)
Air pollution, particularly the presence of PM2.5 particles, remains a global health concern. While Indonesia exhibits lower PM2.5 levels than the global average, vehicular emissions significantly contribute to air pollution. In light of environmental and health considerations, adopting eco-friendly electric motors, mainly interior permanent magnet brushless direct current (IPM BLDC) motors, represents a promising solution for cleaner and more efficient boat propulsion systems, benefiting both the environment and the livelihoods of fishermen. This study thoroughly examines the efficiency and performance of IPM BLDC motors in boat propulsion, utilizing finite element analysis (FEA) through ANSYS Maxwell. The FEA simulations in ANSYS Maxwell were tailored to focus on crucial design variables such as motor torque, speed, and thermal management. It aimed to ensure that the motor specifications meet electric boats’ operational needs in fishing and search operations. Notably, at the desired speed of 5,000 rpm, the motor achieved a torque of 15 Nm with a cogging torque of just 7% and maintained an average efficiency of 89%. Significantly, it operated at a safe temperature without requiring additional cooling systems. Furthermore, simulation outcomes suggested that the motor could effectively function at higher speeds, specifically 6,300 rpm, presenting an exciting opportunity to enhance boat propulsion systems through increased motor speed.